Acid-catalysed treatment of the mallee leaf bio-oil with methanol: Effects of molecular structure of carboxylic acids and esters on their conversion - Hu, Xun; Mourant, Daniel; Wang, Yi; Wu, Liping; Chaiwat, Weerawut; Gunawan, Richard; Gholizadeh, Mortaza; Lievens, Caroline; Garcia-Perez, M.; Li, Chun-Zhu (Elsevier, 2013)
Acid-treatment of the bio-oil from the pyrolysis of mallee leaves in methanol over a solid acid catalystAmberlyst 70 has been investigated in this study. The reactivities of the carboxylic acids with methanolwere quite different over the solid acid catalyst, which was closely related to their distinct molecular structures. The linear alkyl substituted groups, the branched alkyl substituted groups, and the aromatic carbon chain of the acids created the different steric hindrances, which negatively affected their accessibility to the catalytic sites on/in the solid acid catalyst. Similar steric effects were found in the conversion of the heavy esters into small esters via transesterification. In addition to the esterification/transesterification, the methanolysis of the olefin and decomposition of the oligomers in bio-oil occurred simultaneously during the acid treatment, which converted the reactive components into the relatively volatile and stable ones and improved the quality of the bio-oil.